Clinical risk factors to predict deep venous thrombosis post-endovenous laser ablation of saphenous veins. (April 2014) - Chi, Y-W; Woods, T C
Objective: Endovenous laser ablation of saphenous veins is an alternative in treating symptomatic varicose veins. Deep venous thrombosis (DVT) has been reported in up to 7.7% of patients undergoing such procedure. We sought to establish clinical risk factors that predict DVT post-endovenous laser ablation. Method: Patients who underwent endovenous laser ablation were prospectively followed. Clinical data and post-interventional duplex ultrasound were analysed. A P value <0.05 was accepted as representing a significant difference. Results: From 2007 to 2008, 360 consecutive patients were followed. Nineteen DVTs were found on follow-up ultrasound. Eighteen cases involved either the saphenofemoral or saphenopopliteal junctions; only one case involved the deep venous system. Age >66 ( P = 0.007), female gender ( P = 0.048) and prior history of superficial thrombophlebitis (SVT) ( P = 0.002) were associated with increased risk of DVT postprocedure. Conclusion: Age >66, female gender and history of SVT were significant predictors of DVT post-endovenous laser ablation of saphenous veins.